2008
DOI: 10.1002/macp.200800383
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Properties of Alternating Copolymers of N‐Methylmaleimide with Olefins Including Cyclic and Polar Groups

Abstract: The radical alternating copolymerization of N‐methylmaleimide with various olefins was carried out to obtain thermally stable and transparent polymers. Cyclic olefins including an exo‐methylene group showed high polymerization reactivities during the copolymerization. The introduction of a polar substituent into the olefin monomers results in the formation of copolymers with a high yield. The polymerization reactivity of the olefins is discussed based on DFT calculations. The introduction of cyclic and polar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 29 publications
(35 reference statements)
3
33
1
Order By: Relevance
“…Poly(3-alt-IB) was soluble in chloroform, 1,2-dichloroethane, tetrahydrofuran, ethyl acetate, N,N-dimethylformamide, and dimethyl sulfoxide, as previously reported. [26,28] Poly(1/3-alt-IB)s and poly(2/3-alt-IB) including a small content of the 1 and 2 monomer units showed a solubility similar to that of poly(3-alt-IB). …”
Section: Copolymerizationmentioning
confidence: 93%
See 1 more Smart Citation
“…Poly(3-alt-IB) was soluble in chloroform, 1,2-dichloroethane, tetrahydrofuran, ethyl acetate, N,N-dimethylformamide, and dimethyl sulfoxide, as previously reported. [26,28] Poly(1/3-alt-IB)s and poly(2/3-alt-IB) including a small content of the 1 and 2 monomer units showed a solubility similar to that of poly(3-alt-IB). …”
Section: Copolymerizationmentioning
confidence: 93%
“…[21][22][23] Recently, it was reported that the alternating copolymerization of N-alkylmaleimides (RMI) with isobutene (IB) produced high-molecular-weight copolymers [poly(RMIalt-IB)s] with excellent thermal stabilities, as well as excellent mechanical and optical properties. [24][25][26][27][28][29][30] For example, the onset temperature of the thermal decomposition was over 350 8C and the glass transition temperature (T g ) was 152 8C for poly(RMI-alt-IB) with an N-methyl substituent. [24] The mechanical and optical properties were also reported to be similar or superior to conventional transparent polymeric materials, such as poly-(methyl methacrylate) and polycarbonate bisphenol-A; the flexural strength and modulus were 137 MPa and 4.81 GPa, and the refractive index and Abbe's number were 1.53 and 51, respectively, for the same poly(RMI-alt-IB).…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] The introduction of polar groups and cyclic structures into the olefin repeating units led to further increases in their thermally stability and the T g values. [14][15][16] Recently, we demonstrated that the copolymerization of the RMIs provided copolymers with finely controlled structures in the 1:1 alternating and 2:1 sequence-controlled fashions, depending on the steric bulkiness and conjugated structure of olefin and styrene derivatives. [17,18] The sophisticated AAB-type sequence structures were produced during the copolymerization under penultimate unit control (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic peaks observed in this study were similar to those for the alternating copolymers obtained by the copolymerization of various RMIs and IB. [18][19][20][21][22][23][24][25] In the spectrum shown in Figure 1, no peak was detected for the unreacted maleimide residue, although it is expected to be observed at 6.72 ppm if the allyl group of the AMI K. Takeda, A. Matsumoto Table 1. Radical copolymerization of AMI with IB in 1,2-dichloroethane at 30 8C a) .…”
Section: Resultsmentioning
confidence: 99%
“…Doi et al and we have already reported various kinds of alternating copolymers of N-alkylmaleimides (RMI) with isobutene (IB) [poly(RMI-alt-IB)s] having excellent thermal stabilities, as well as excellent mechanical and optical properties. [18][19][20][21][22][23][24][25] The poly(AMI-alt-IB) obtained in the present study includes an unsaturated group in the N-substituent, which is curable We synthesized an alternating copolymer of N-allylmaleimide (AMI) and isobutene (IB) [poly(AMI-alt-IB)] as a new class of thermosetting polymers by the free radical copolymerization process. The reactivity of the maleimide group of the AMI monomer was evaluated to be 10 3 times higher than that of the N-allyl group based on the results for the ternary copolymerization system composed of N-methylmaleimide (MMI), N-allylphthalimide (AP), and IB.…”
Section: Introductionmentioning
confidence: 99%